The impact of preoperative biliary drainage on bile colonization of patients undergoing pancreaticoduodenectomy - Yifei Yang; Yichen Duan; Chengxiang Su; Jianjie Sheng; Linxi Zhu; Yu Xie; Haobai Liu; Neng Tang; Yudong Qiu; Chenglin Lu; Chuang Chen; Liang Mao; et al. (Annals of Medicine)
Background Preoperative biliary drainage (PBD) may be performed for jaundiced patients with periampullary tumors. This study aimed to evaluate the impact of PBD on biliary microbiome and perioperative complications in patients undergoing pancreaticoduodenectomy (PD).Methods This retrospective study enrolled 323 patients who underwent PD between March 2018 and March 2024. Intraoperative bile specimens were obtained for microbiological analysis of species identification and antimicrobial resistance patterns..Results PBD was performed in 191 (59.1%) of the 323 patients. Organ/space surgical site infection (SSI) (51.8% vs 37.9%, p < 0.001) and bacterial colonization of bile (90.6% vs 28.0%, p < 0.001) were significantly more frequent in patients with PBD. PBD was identified as an independent risk factor of organ/space SSI (OR = 1.837, 95% CI: 1.158–2.916, p = 0.010) and associated with increased contamination with polymicrobial mixed flora (47.1% vs 4.5%, p < 0.001), K. pneumoniae (23.6% vs 0.8%, p < 0.001), E. faecalis (14.1% vs 1.5%, p < 0.001), E. faecium (6.8% vs 0.8%, p = 0.009). This shift corresponded to higher resistance to piperacillin–tazobactam (23.1% vs 0.0%, p = 0.038), cefoperazone–sulbactam (25.3% vs 0.0%, p = 0.021), ciprofloxacin (36.1% vs 6.3%, p = 0.006), and levofloxacin (47.4% vs 4.8%, p < 0.001). Patients with positive bile culture had a significantly higher occurrence of organ/space SSI than the negative group (53.3% vs 32.7%, p < 0.001). K. pneumoniae was identified as an independent risk factor for organ/space SSI (OR = 2.636, 95% CI: 1.353–5.137, p = 0.004).Conclusions There were fundamental differences in the bile microbiome profile and antibiotic resistance of patients with/without PBD. These findings suggest that adjusting perioperative antibiotic regimens based on biliary culture may be warranted.